Global stratigraphy, palaeobiogeography and palaeoecology of Albian-Maastrichtian pithonellid calcispheres: impact on Tethys configuration - Dias-Brito, D. (Academic Press Ltd, 2000)
This study reviews the stratigraphy, palaeobiogeography and palaeoecology of some important Albian-Maastrichtian pelagic calcispheres: Bonetocardiella conoidea, Pithonella ovalis, P. perlonga, P. sphaerica and P. trejoi. It also presents a significant new data set on these organisms from the western South Atlantic Ocean. The group reached its acme simultaneously all over the world during the highest Cretaceous sea level in late Albian to Coniacian times. A strong association also existed between the maximum temperature and the salinity of the Tethyan water mass and the climax of these opportunistic microfossils. Their remarkable presence along the Brazilian and west African margins during the Albian, in association with other typical Tethyan pelagic biotic elements, indicates that during this period the northern South Atlantic was a long, narrow arm of the Tethys Sea. (C) 2000 Academic Press.
Keywords: Cretaceous; calcispheres; Calcisphaerulidae; Pithonelloideae; pithonellids; biostratigraphy; palaeobiogeography; palaeoecology; palaeoceanography; Tethys; South Atlantic; fine-grained carbonates; marginal seas; epicontinental seas